2002
DOI: 10.1128/jcm.40.9.3286-3290.2002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Anaplasma marginale and a New Ehrlichia Species Closely Related to Ehrlichia chaffeensis by Sequence Analyses of 16S Ribosomal DNA in Boophilus microplus Ticks from Tibet

Abstract: To identify ehrlichial agents in Boophilus microplus ticks, DNA samples of B. microplus collected from the Tibet Autonomous Region and Sichuan Province of China were screened by a nested PCR. Sixteen of 43 (37%) DNA samples of B. microplus from Tibet were positive in nested PCR analysis. All 27 samples from Sichuan were negative. The screen identified two ehrlichial agents based on different 16S rRNA genes that were found after amplifying and sequencing the 5-end fragments of the 16S rRNA genes. One sequence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 17 publications
2
81
0
1
Order By: Relevance
“…Although the I. persculcatus group that transmits A. phagocytophilum is present in South Korea, the classical tick vector for E. chaffeensis, Amblyomma americanum, is not. However, E. chaffeensis or a similar species has been detected in Amblyomma testudinarium and Haemaphysalis yeni ticks in South China (7), Boophilus microplus ticks in Tibet (27), and Ixodes ovatus ticks in Japan (23); and we have found evidence of both E. chaffeensis and A. phagocytophilum in both Haemaphysalis longicornis and I. persulcatus ticks from South Korea (17a). Although a definitive role of these causative agents and potential tick vectors in human infections cannot be assumed from these data, the presence of the causative agents and potential tick vectors with the capacity to bite humans suggests that the serological data reflect a previously unrecognized but emerging problem in South Korea and perhaps more broadly across Asia.…”
Section: Discussionmentioning
confidence: 96%
“…Although the I. persculcatus group that transmits A. phagocytophilum is present in South Korea, the classical tick vector for E. chaffeensis, Amblyomma americanum, is not. However, E. chaffeensis or a similar species has been detected in Amblyomma testudinarium and Haemaphysalis yeni ticks in South China (7), Boophilus microplus ticks in Tibet (27), and Ixodes ovatus ticks in Japan (23); and we have found evidence of both E. chaffeensis and A. phagocytophilum in both Haemaphysalis longicornis and I. persulcatus ticks from South Korea (17a). Although a definitive role of these causative agents and potential tick vectors in human infections cannot be assumed from these data, the presence of the causative agents and potential tick vectors with the capacity to bite humans suggests that the serological data reflect a previously unrecognized but emerging problem in South Korea and perhaps more broadly across Asia.…”
Section: Discussionmentioning
confidence: 96%
“…Within the family Anaplasmataceae, there is at present no consensus as to the degree of 16S rRNA gene dissimilarity which should be evident to distinguish two bacterial species as opposed to that which should be evident to represent natural genetic variation. A recent study suggested that 0.5% divergence in the 16S RNA gene sequence of bacteria within this family could be considered a cutoff (29); however, it seems prudent to await phylogenetic studies based on sequences of other genes before such a recommendation is accepted.…”
Section: Discussionmentioning
confidence: 99%
“…strain EBm52 was shown to be closely related to Ehrlichia sp. strain Tibet (99.9% sequence similarity) identified in B. microplus ticks collected in Tibet (29). The latter ehrlichia was recently presented as a new species within the genus Ehrlichia, based on phylogenetic analyses of the 16S rRNA gene (29).…”
Section: Discussionmentioning
confidence: 99%
“…The nested PCR for A. phagocytophilum 16S rRNA genes was performed as described previously. 8 Briefly, Anaplasma genus-specific primers of outer-1 (5 -TTG AGA GTT TGA TCC TGG CTC AGA ACG-3 )/outer-2 (5 -CAC CTC TAC ACT AGG AAT TCC GCT ATC-3 ) were used in the first round of amplification, and species-specific primers of HGA1 (5 -GTC GAA CGG ATT ATT CTT TAT AGC TTG -3 )/HGA2 (5 -TAT AGG TAC CGT CAT TAT CTT CCC TAC-3 ) were used for nested PCR. A final 389-bp DNA fragment was produced.…”
Section: Methodsmentioning
confidence: 99%